KARAKTERISKTIK BRIKET ARANG DARI KAYU AKASIA (ACACIA MANGIUM WILLD) SEBAGAI ENERGI TERBARUKAN - Lilis Sihombing; Alpian Alpian; Sari Mayawati; Jumri Jumri; Wahyu Supriyati (Jurnal Teknologi Berkelanjutan, 2020)
Charcoal briquettes can be alternative energy and can be produced from A. mangium wood. This type of wood is commonly found in Central Kalimantan. The purpose of the study was to determine the characteristics of charcoal briquettes produced from A. mangium wood stems, branches, and twigs that referred to the Indonesian National Standard (SNI-01-6235-2000) using a Completely Randomized Design method with a total sample of 15 pieces. The data obtained were tested for homogeneity using the SPSS application and statistically analyzed using the Analysis of variance (Anova). The treatment had a significant effect, then continued with Duncan's Closest Real Distance Test. The results obtained generally meet the Indonesian National Standard (SNI-01-6235-2000) regarding charcoal briquettes except for water content, ash content, and volatile substances. The best data from the stems, branches, and twigs of A. mangium was the stem which produced 8.94% moisture content, higher density of 0.73g/cm3, ash content of 12.60%, bound carbon of 50, 60%, volatile matter content of 27.86%, compressive strength of 65.06 kg/cm2 and calorific value of 6923.08 cal/g.